2008
DOI: 10.1071/sb07031
|View full text |Cite
|
Sign up to set email alerts
|

Elaeocarpus sedentarius sp. nov. (Elaeocarpaceae)—morphometric analysis of a new, rare species from eastern Australia

Abstract: To assess the status of a putative new species of Elaeocarpus L. (Elaeocarpaceae) from north-eastern New South Wales (NSW), with respect to the morphologically similar E. blepharoceras Schltr. from New Guinea, we undertook morphometric analysis of 11 vegetative attributes measured on 11 specimens of the putative new species and eight of E. blepharoceras. Cluster analysis (flexible UPGMA) and ordination (PCC) separates highland specimens of E. blepharoceras from the NSW material plus lowland E. blepharoceras. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The previous study reported that several molecular phylogenetic studies on the families Elaeocarpaceae, as well as the genus Elaeocarpus, have been undertaken. The molecular studies using full sequence data from the Internal Transcribed Spacer (ITS) of nuclear ribosomal DNA (Maynard 2008). Zeng et al (2005) reported that phylogenetic relationships within families Moraceae have also used the 5.8S rRNA to predict phylogenetic of intra-species and inter-species within genus Morus (Moraceae).…”
Section: Gonystylusmentioning
confidence: 99%
“…The previous study reported that several molecular phylogenetic studies on the families Elaeocarpaceae, as well as the genus Elaeocarpus, have been undertaken. The molecular studies using full sequence data from the Internal Transcribed Spacer (ITS) of nuclear ribosomal DNA (Maynard 2008). Zeng et al (2005) reported that phylogenetic relationships within families Moraceae have also used the 5.8S rRNA to predict phylogenetic of intra-species and inter-species within genus Morus (Moraceae).…”
Section: Gonystylusmentioning
confidence: 99%
“…Rawlings and Ladiges 2001, Burke and Adams 2002, Flann et al 2008, Giles et al 2008, Maynard et al 2008. The three numerical techniques used here to evaluate the S. dichotrianthus-S. phillyreoides complex have been unable to conclusively separate specimens identified either as S. dichotrianthus or S. phillyreoides, or re-organize specimens in different taxonomic ranks as subspecies or variety, or separate them by geographical distribution, or confirm the variety described by Rizzini (1982).…”
Section: ]mentioning
confidence: 53%
“…The distance matrix was calculated by using Gower metric association measure (Gower, 1971). Gower has a built-in range-standardized method that is more suitable for constructing matrices when a mixture of two-state, multistate and quantitative data are present in a data set, because it gives them an equal weight (Gower 1971, Sneath and Sokal 1973, Milligan and Cooper 1988, Stuessy 1990, Crisp and Westo, 1993, Belbin 2006, Maynard et al 2008, particularly if there is a moderate proportion of missing characters (Belbin 2006). It is also able to analyze large data sets (Belbin 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations